Vietnam : A Handwashing Behavior Change Journey for the Caretakers’ Program - World Bank (Washington, DC, 2012)
The Vietnam Handwashing Initiative (HWI) was launched in January 2006 by the Ministry of Health (MoH) with funds from the Danish Embassy in Vietnam and technical assistance from the Water and Sanitation Program (WSP). This learning note documents the development process of the caretakers' program with a focus on how it was designed, implemented, and monitored. Lessons learned and challenges are also highlighted to assist program managers in designing and managing evidence-based handwashing with soap or other hygiene promotion programs. A separate publication will focus on the process of developing the children's handwashing program.